Influence of food packaging color and foods type on consumer purchase intention: the mediating role of perceived fluency - Su, Jie; Wang, Shuqi (Frontiers in Nutrition, 2024)
Packaging color entices and influences consumer perceptions and significantly affects the identification of products. Marketers manipulate the exterior packaging to influence consumer expectations, experiences, and behaviors. Building upon psychological literature on colors and emotions, we explored the influence of food packaging color and food type on consumers’ purchase intentions. Study 1 explored the interaction effects between food packaging color (warm vs. cold) and food type (vice foods vs. virtue foods) on consumers’ purchase intentions. Study 2 examined whether perceived fluency mediates the interaction effect of food packaging color and food type on consumers’ purchase intentions. The results showed that for vice foods, characterized by tastiness but unhealthiness, the utilization of warm-colored food packaging enhances consumer purchase intent. In contrast, for virtue foods that are healthful but lack gustatory appeal, the use of cold food packaging colors will lead to higher consumer purchase intent. Perceived fluency mediates the interaction effect of food packaging color and food type on consumers’ purchase intentions. This study will assist marketers to exploring a range of possibilities for packing color, impacting both the physiological and cognitive dimensions of consumer behavior related to food products, and offering practical implications for market managers.